Teachers’ Roles in Overcoming Difficulties in Learning English of Junior High Students in Special Needs Schools (SLB) at Bengkulu City - Desva Andusti; Kiagus Baluqiah; Washlurachim Safitri; Agung Suhadi (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study aims to find out teachers roles in overcoming difficulties in learning English of junior high students special needs schools (SLB) at Bengkulu city. The background of this problem arises because SLB students still face difficulties in learning English, while the role of teachers in overcoming these difficulties has not been clearly described. The research method used is descriptive qualitative with Observation Sheet and Question Lists instruments. The results of the study show that 10 teacher roles according to Harmer in (Naibaho, 2019) are applied in teaching English to overcome the difficulties of learning English for junior high students in Special Needs Schools (SLB) in Bengkulu City. However, the level of implementation varies depending on the classroom context and student needs. There are 10 teacher roles in teaching children with special needs, namely (1) controller (2) organizer (3) assessor (4) prompter (5) participant (6) resource (7) tutor (8) observer (9) performer and (10) teaching aids. Teachers carry out these roles in overcoming students' learning difficulties by guiding each student with special needs individually, repeating instructions and materials gradually, managing the class in a structured manner, providing direct examples through gestures and facial expressions, and using learning media that are appropriate to the conditions and needs of students. Researchers suggest that English teachers in special needs schools continue to optimize their roles in learning, because teaching students with special needs requires appropriate and consistent strategies. For future researchers who are interested in conducting similar research, it is recommended to conduct a more in depth analysis of the implementation of each teacher's role and also at other levels of education.